How to learn vocabulary effectively in English language learning (Eurasian Journal of Learning and Academic Teaching, 2022)
Vocabulary is an important focus of literacy teaching and is a key to acquire English language. It refers to the knowledge or words, as well as their structure, morphology, use, grammar, meanings, semantics, and links to other words. This article highlights the ways of to learning vocabulary, how to develop effective vocabulary learning skills; explore some of the examined techniques to achieve fluency faster.